Diagnostic evaluation and cardiopulmonary exercise test findings in young athletes with persistent symptoms following COVID-19 - Moulson, N.; Gustus, S. K.; Scirica, C.; Petek, B. J.; Vanatta, C.; Churchill, T. W.; Guseh, J. S.; Baggish, A.; Wasfy, M. M. (British Journal of Sports Medicine, 2022)
Objectives Persistent or late-onset cardiopulmonary symptoms following COVID-19 may occur in athletes despite a benign initial course. We examined the yield of cardiac evaluation, including cardiopulmonary exercise testing (CPET), in athletes with cardiopulmonary symptoms after COVID-19, compared CPETs in these athletes and those without COVID-19 and evaluated longitudinal changes in CPET with improvement in symptoms.